A novel analysis model for optimization performance of Bernoulli serial production system considering rework processes. (January 2020) - Zhou, Binghai; Lin, Song
Production system modeling aims to investigate the principles of production procedures and to reveal the relationship between components and systems. Tremendous efforts have been devoted to production system modeling for the serial production system. However, most of the research focuses on the analysis of the systems at the steady state. Due to the emphasis of the quality management, production systems with rework loops are widely used in today's manufacturing industrials, which the traditional approaches are not applicable to. Since the recent analysis of transients shows significant value and great potential in manufacturing systems, in this article, a new mechanism for rework is introduced based on the principles of quality management and lean production. A novel "Instant-Checking" method is developed to model Bernoulli serial production system considering rework loops. This method overcomes conventional restrictions and limited assumptions, and it extends the problem to systems with complex structures. Meanwhile, the analysis for transients is conducted to demonstrate relationships between component- and system-level characteristics. Finally, numerical experiments are performed to verify the effectiveness of the model.